Combined NMR and UV-Vis Spectroscopic Studies of Models for the Hydrogen Bond System in the Active Site of Photoactive Yellow Protein: H-Bond Cooperativity and Medium Effects - Koeppe, Benjamin; Tolstoy, Peter M.; Guo, Jing; Denisov, Gleb S.; Limbach, Hans-Heinrich (Journal of Physical Chemistry B, 2021)
Intramolecular hydrogen bonds in aprotic media were studied by combined (simultaneous) NMR and UV-vis spectroscopy. The species under investigation were anionic and featured single or coupled H-bonds between, for example, carboxylic groups and phenolic oxygen atoms (COO···H···OC)-, among phenolic oxygen atoms (CO···H···OC)-, and hydrogen bond chains between a carboxylic group and two phenolic oxygen atoms (COO···H···(OC)···H···OC)-. The last anion may be regarded as a small molecule model for the hydrogen bond system in the active site of wild-type photoactive yellow protein (PYP) while the others mimic the corresponding H-bonds in site-selective mutants. Proton positions in isolated hydrogen bonds and hydrogen bond chains were assessed by calculations for vacuum conditions and spectroscopically for the two media, CD2Cl2 and the liquefied gas mixture CDClF2/CDF3 at low temperatures. NMR parameters allow for the estimation of time-averaged H-bond geometries, and optical spectra give additional information about geometry distributions. Comparison of the results from the various systems revealed the effects of the formation of hydrogen bond chains and changes of medium conditions on the geometry of individual H-bonds. In particular, the proton in a hydrogen bond to a carboxylic group shifts from the phenolic oxygen atom in the system COO-···H-OC to the carboxylic group in COO-H···(OC)-···H-OC as a result of hydrogen bond formation to the additional phenolic donor. Increase in medium polarity may, however, induce the conversion of a structure of a type COO-H···(OC)-···H-OC to the type COO-···H-(OC)···H-OC. Application of these results obtained from the model systems to PYP suggests that both cooperative effects within the hydrogen bond chain and a low-polarity protein environment are prerequisites for the stabilization of negative charge on the cofactor and hence for the spectral tuning of the photoreceptor.
CRIS-Team Scopus Importer:2022-08-03